Larvicidal and adulticidal effects of combined hydroethanolic extracts of clove flower buds and garlic bulbs on Anopheles gambiae - Charles O. Nwonuma; Temitope E. Elleke; Adedapo O.Adeogun; Teslim A. Lawal; Babasoji P. Omoniwa; Anthony B. Ojekale (Malaria Journal)
Abstract Background Insecticides are toxic substances, though not necessarily toxins, intentionally released into the environment to kill or manage insect populations. These chemical toxins pose significant risks to human and animal health due to their direct effects and their impact as environmental pollutants. To mitigate these chemical hazards, the use of phytocompounds with superior larvicidal or mosquitocidal effects, low toxicity levels in mammals, and short-term environmental persistence may be a preferable alternative. Methods This study aimed to evaluate the larvicidal and adulticidal effects of the combined hydroethanolic extracts of garlic and clove on Anopheles gambiae. The experiment included four treatment groups: garlic, clove, combined extract (garlic + clove), and deltamethrin (standard insecticide). At the end of the 24 h experiment, the knocked-down adult mosquitoes were homogenized and used for biochemical assays. Results The combined garlic-clove extract significantly increased (p < 0.05) the larval mortality rate compared to the single garlic and clove extracts. Similarly, the combined extracts of garlic-clove significantly increased (p < 0.05) mortality of adult mosquitoes compared to deltamethrin and the individual garlic and clove extract. The garlic-clove combined extracts showed a significant decrease (p < 0.05) in the activity of acetylcholine esterase and Na–k ATPase compared with the deltamethrin group. Furthermore, the docking interaction between AChE and voltage gated ion channel with the GC–MS identified compounds of the extracts showed a higher binding affinity with caryophyllene, estrone, morellinol compared to deltamethrin. Conclusions The efficacy of the garlic-clove extract as a larvicide and adulticide has been confirmed through biochemical analyses and in silico studies. This lethal effect is likely due to the inhibition of crucial enzymes that facilitate essential processes such as signal transduction and energy production. Moreover, the biocidal properties of these extracts stem from the alteration of vital metabolic pathways, influenced by a range of bioactive compounds found in both garlic and clove.